Interactive Multimedia Based on Contextual Approach in Mathematics Subjects for Fourth Grade of Elementary Schools - Widiari, Ni Kadek Sri; Wiarta, I Wayan (Jurnal Pedagogi dan Pembelajaran, 2024)
Mathematics is one of the subjects that is often encountered and has an important role in everyday life. Mathematics lessons will always be found at every level of education, both in elementary school and in college. This development research was motivated by the problem of a lack of learning media that could increase students' interest and motivation in learning activities. This research aims to analyze the effectiveness of interactive multimedia based on a contextual approach in fourth grade elementary school mathematics subjects. This development research uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of this research were 3 experts and 32 fourth grade elementary school students. The data collection methods used were observation, interviews, questionnaires and tests. Data collection instruments use questionnaires and multiplechoice tests. The data analysis techniques in this research are qualitative descriptive analysis, quantitative descriptive analysis, descriptive statistical analysis, inferential descriptive analysis. Based on the results of the t test, H0 is rejected and Ha is accepted. Thus, it can be concluded that interactive multimedia based on a contextual approach is feasible and effective for use in mathematics subjects with equal fraction material for fourth grade students in elementary school. The implications of this research are expected to help teachers provide mathematics learning that is fun and easy for students to understand.